Peran Dinas Pemberdayaan Perempuan Dan Perlindungan Anak Dalam Pencegahan Kekerasan Terhadap Perempuan Dan Anak Di Maluku Utara - Arfah, Rusdi; Husein, Muhammad Ar; Alhadar, Muhdi (Peneliti.net, 2024)
Today's development of women's problems and the protection of children's rights, they are important, various conditions of children have shown that, it turns out that children are still in a condition of concern, because they are in a position in the range of crime problems, and are very prone to become victims of existing shipments or they are also prone to recognize or criminal acts that also exist. The most important issue apart from the prevention and handling process is to analyze the causes of violence so that the prevention and handling process can later be in accordance with the objectives of policy implementation. Therefore, the importance of implementing women and children protection policies is an interesting thing to be examined at the Office of Women's Empowerment and Child Protection of North Maluku Province.